Diabetic retinopathy and cardiovascular disease - Sabanayagam, Charumathi; Wong, Tien Yin (Basel : Karger, 2019)
Diabetic retinopathy (DR), a common microvascular complication, has consistently been shown to be associated with an increased risk of cardiovascular disease (CVD). This book provides complete coverage of DR as a potential marker for CVD in those with diabetes. It succinctly reviews the epidemiological and pathogenic links of DR to various cardiovascular events including stroke, coronary artery disease, chronic kidney disease, heart failure, and mortality. Furthermore, it discusses the usefulness of DR in CVD risk prediction and cardiovascular safety of anti-VEGF therapy in diabetic patients. There are insights from contemporary diabetic trials that demonstrated the enhanced cardiovascular benefit of novel glucose lowering therapy. It also highlights the potential of novel retinal imaging to predict CVD and its risk factors using the state-of-the art artificial intelligence-based deep learning systems. This book will be an invaluable resource for specialists translating research findings into clinical care, including those in cardiology, endocrinology, ophthalmology, and general practitioners. IT will also be of interest to public health practitioners, researchers, graduate students, and biotech companies interested in developing retinal image-based diagnostic and prognostic tools.
Keywords: RETINOPATÍA DIABÉTICA -- COMPLICACIONES; SISTEMA CARDIOVASCULAR -- ENFERMEDADES -- COMPLICACIONES; SISTEMA CARDIOVASCULAR -- ENFERMEDADES -- FACTORES DE RIESGO